Enhancing Students’ Speaking Skills Through Animation-Based Learning in EFL Classroom. (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aimed to improve students’ speaking skills through animation-based learning in a first-grade EFL classroom at SMP Darul Amin. The study employed Classroom Action Research (CAR) consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. The participants were 30 first-grade junior high school students. The instruments used in this study were observation sheets, speaking performance tests, and documentation. The findings revealed that animation-based learning successfully improved students’ speaking skills, classroom participation, confidence, and motivation during the learning process. The students’ average speaking score increased from 48.13 in the pre-action stage to 76.53 in Cycle I and further improved to 87.56 in Cycle II. In addition, the percentage of students achieving the Minimum Mastery Criterion (KKM) increased from 10% in the pre-action stage to 90% in Cycle II. Therefore, animation-based learning can be considered an effective learning media to improve students’ speaking skills in EFL classrooms.